PENGARUH KEPEMIMPINANTRANSFORMASIONAL TERHADAP PENERAPAN MANAJEMEN PENGETAHUAN DENGAN BUDAYA MARKET SEBAGAI VARIABEL MODERATOR - WICAKSONO, SATRIAWAN (Jurnal Ilmu Manajemen (JIM), 2014)
Abstract:.The level of business competition in the 21th century increase along with free trade occured. It encourageeach organization to maintain their competitive advantages.Knowledgeis the main factor to reach competitive advantageswhich obtainable from knowledge management process.This study aims to examine and analyze whether the influence oftransformational leadershipknowledge management at East Service and repair Office PT. Telekomunikasi Indonesia,Tbk and moderating effect of organizational culture on thisrelationship.Thesampling technique of this study is using proportionate stratified random sampling with sample size of67respondents. Statistical analysis method was used Partial Least Square (PLS) with the help of the SMART PLS and SPSS 17.0 software. Based on the result of analysis showed that transformational leadership has positive effect and significant impact on the knowledge sharing with value t-statistics.Market culture has not moderate the relationship between transformational leadership on knowledge management with a value t-statistics. Keywords:transformational leadership, knowledge management, organizational culture